If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -23 = 9 Reorder the terms: -23 + y = 9 Solving -23 + y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + y = 9 + 23 Combine like terms: -23 + 23 = 0 0 + y = 9 + 23 y = 9 + 23 Combine like terms: 9 + 23 = 32 y = 32 Simplifying y = 32
| -5.8(3t+5)-2.5(2t-6)= | | 5x-2(-2y+4x)-5y= | | log(3x-2)5=3 | | -5t^2+20t-25=0 | | 100[0.06(z+3)]= | | 360=25-2+20x-1 | | 2x=8x-43 | | 2x^2-x=x | | 4x-40+6x=180 | | 360=25x+1 | | (t-6)(t+9)=0 | | 9c=dforc | | 2x-100=20 | | 19+(-32)= | | 2-x-5=-3x+2(x-1) | | 1.2=3sinx+1 | | 65x=130 | | 3/8x-y=-2 | | 8x+6y=11 | | 8x-6y=84 | | 2(2x-(4-7y+6x)+5y)= | | h^2+6h-23=0 | | 3x+15=45+x | | 20x+30=180 | | (3x-4x+2y)*(2y+3y+2x)= | | -2x-5(x+1)=-x | | 6e^3x=30 | | 11[5-(4-2x)]+10x=4(8x+4)-5 | | w(26)=3x-1 | | xFactor+3x+2=0 | | y=.5x+-19 | | 5x-36=34+4x |